A deductive object-oriented approach to geographic information systems - Wiboon Promphanich; Vilas Wuwongse; Zhao, Ming; Surapong Auwatanamongkol; The Goverment of the Republic of Germany (Bangkok : Asian Institute of Technology, 1991)
This thesis study is aimed at the proposal of a deductive object-oriented data model which is based upon the specific characteristics and requirements of geographic information systems. Geographic information system is the one which involves the creation, storage, retrieval, browsing and management of electronic form of map entities. Various basic object concepts are formulated under the framework of deductive object-oriented paradigm. In this model the spatial entity are modeled as an instance of subclass of class Point, Line, Polygon or the existing subclasses of these classes. The spatial entity inherits the property of superclass and includes its own properties. These spatial entities are associated with maps. The other type of of the map is overlay which derived from the existing maps. The overlay is modeled as a rule which stored in the intensional database. The model provides the data definition and the data manipulation language. This language is modified from the SQL. The language includes the command for the user to create, insert, delete, and update both the data and the rule.
A thesis report submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1991
Keywords: GIS (Computer program)